2017
DOI: 10.5194/os-2017-95
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating downwelling solar irradiance at the surface of the tropical Atlantic Ocean: A comparison of PIRATA measurements against several re-analyses and satellite-derived data sets

Abstract: Abstract. 15This paper assesses the merits and drawbacks of several data sets of the solar downwelling radiation received at the surface of the tropical Atlantic Ocean where the field of solar radiation is hardly known. The data sets are compared to qualified measurements of hourly irradiance made at five buoys of the PIRATA network for the period 2012-2013. The data sets comprise the re-analyses MERRA-2 and ERA-5 and three satellite-derived data sets: HelioClim 3v5, SARAH 2 and CAMS Radiation Service v2. The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Bell et al (2009), Bengulescu et al (2016Bengulescu et al ( , 2018, Blanc et al (2011Blanc et al ( , 2015, Lefèvre et al (2007), Wahab et al (2009). Solar radiation is also a crucial factor which influences life on Earth for animals, plants (Bois et al, 2008;Colombo et al, 2009;Wagner et al, 2012) and humans (Juzeniene et al, 2011). The energy received from the Sun and impinging on a horizontal surface of unit surface located at ground level is called the surface solar downward irradiation and is abbreviated as SSI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bell et al (2009), Bengulescu et al (2016Bengulescu et al ( , 2018, Blanc et al (2011Blanc et al ( , 2015, Lefèvre et al (2007), Wahab et al (2009). Solar radiation is also a crucial factor which influences life on Earth for animals, plants (Bois et al, 2008;Colombo et al, 2009;Wagner et al, 2012) and humans (Juzeniene et al, 2011). The energy received from the Sun and impinging on a horizontal surface of unit surface located at ground level is called the surface solar downward irradiation and is abbreviated as SSI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, meteorological reanalyses offer estimates of SSI covering the whole world that span several decades back in time. Boilley and Wald (2015), Bengulescu et al (2017) and Trolliet et al (2017) have analyzed the quality of several reanalyses: ERA-Interim, ERA-5, MERRA, and MERRA-2, against ground measurements of SSI. These authors reported that re- Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a practical advantage to this approach as broadband radiation is accurately estimable from satellite images (Blanc et al, 2011;Lefèvre et al, 2014). Alternate sources of data on broadband radiation are meteorological analyses or forecasts though their quality is poorer than that of satellite-derived data (Boilley and Wald, 2015;Bengulescu et al, 2017;Trolliet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Too many stations may result in an over-investment with a negligible scientific gain; too few stations may lead to a misrepresentation of the spatial variability of the variables of interest, with possible biases in analyses and interpretation of the measurements. Techniques have been proposed for the optimal design of networks of measuring stations at ground (Bogárdi et al, 1985;Bras and Rodríguez-Iturbe, 1976;Stauffer et al, 2000;Vinnikov et al, 1999). They are often based on the analysis of a priori knowledge of the spatial correlation and more generally of the geostatistical properties of the variables of interest and the space and timescales to study.…”
Section: Introductionmentioning
confidence: 99%